LONG WAVES, INSTITUTIONAL CHANGES, AND HISTORICAL TRENDS: A STUDY OF THE LONG-TERM MOVEMENT OF THE PROFIT RATE IN THECAPITALIST WORLD-ECONOMY - Minqi Li; Feng Xiao; Andong Zhu (Journal of World-Systems Research, 2015)
In this paper we study the long-term movement of the profit rate and related variables in the UK, the US, Japan, and the Euro-zone. Since the mid-19th century there have been four long waves in the movement of the average profit rate and rate of accumulation. The average profit rate tended to fall between the late 19th century and the late 20th / early 21st century. The average profit share fell substantially in the transition from the UK hegemony to the US hegemony. The fall of the profit rateand profit share reflected rising wage and taxation costs. Our findings raise important questions regarding the future development of the capitalist world economy.